Analisis Ketenagakerjaan di Provinsi Jawa Timur - Argus Baskoro; Kuntoro Kuntoro (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2017)
This study aims to analyze the labor force, labor force participation rate, and employment opportunities in East Java. The method used is the observation of secondary data from the Planning and Development Agencies of East Java (BAPPEDA JATIM) and also the central website of the National Bureau of Statistic (BPS). Then, data is analyzed and processed using Spectrum software. The result of labor force data analysis shows that the city of Surabaya is the region with the largest labor force that is 1.336.932 people, while the city of Mojokerto has the lowest number of labor force is 61.459 inhabitants. The total labor force in an area is affected by the number of indigenous peoples and the rate of urbanization, which residents hope to obtain better education and employment. The highest labor force participation rate was found in Pacitan district area of 83%, while the lowest was Probolinggo district at 63%. The highest employment data analysis result is found Surabaya city with the number of 1.245.542 job opportunities. Some of the factors that affect employment opportunities include the economic conditions of an area, population growth rate, resource quality, the amount of income, and age structure of the population.